Integrative multi-omics analysis reveals the potential mechanism by which Streptomyces pactum Act12 enhances wheat root drought tolerance by coordinating phytohormones and metabolic pathways - Jinhui Zhang; Hongwei Wen; Shanshan Wang; Yuzhi Wang; Zeyu Wang; Xingwei Zheng; Jie Chen; Bin Yang; Hao Shan (BMC Plant Biology)
Abstract Background Drought stress is one of the major abiotic stresses that limit wheat growth and yield. Streptomyces, a class of plant growth-promoting rhizobacteria (PGPR) with multifarious metabolic potential and remarkable stress resistance properties in soil, have significant potential in enhancing the drought tolerance of crops. However, the molecular mechanisms by which Streptomyces improve the drought tolerance function of the wheat root are poorly understood. Results In this study, we investigated the role and molecular mechanisms of Streptomyces pactum Act12 in regulating the drought tolerance of wheat root by combining pot experiments and multi-omics techniques. The pot experiment results demonstrated that under drought stress, Act12 treatment significantly promoted the development of the wheat root system, including the total root length, surface area, number of root tips, and diameter. Furthermore, Act12 treatment increased the activity of antioxidant enzymes (SOD activity increased by 23.7%), the content of osmotic regulators proline (265.8%) and soluble protein (116.8%), and significantly decreased the content of malondialdehyde (39.0%). The integrated analysis of the transcriptome and metabolome demonstrated that Act12 might promote root development through the synergistic regulation of phytohormone signaling. Concurrently, it might optimize energy supply and enhance the stability of cell membranes via the regulation of metabolic pathways, including glycolysis, the tricarboxylic acid (TCA) cycle, and glycerophospholipid metabolism. Conclusion Consequently, Act12 enhanced the drought adaptability of the wheat root system from multiple perspectives. This study reveals the central role of Act12 in the regulation of drought resistance in plants and provides a theoretical basis for the development of drought-resistant biologics based on Streptomyces.